A camel anti-lysozyme CDR3 only domain antibody selected from phage display VHH library acts as potent lysozyme inhibitor. (5th May 2017) - Qiu, Lingling; Feng, Yaning; Ma, Xiaoling; Li, Jiangwei
Abstract: Mimetics of antibody-binding sites represent particularly interesting targets, however they are difficult to identify. In most cases, naturally derived CDR3 peptides show a much lower activity and affinity. In this study, we identified a CDR3 domain antibody with framework 3 (FR3) and FR4 in the flank by screening a lysozyme-immunized phage display VHH library. This antibody has a potent enzyme inhibiting activity and high thermal stability. With sequence alignment and site-directed mutagenic analysis, we found that the cysteine residue at amino acid position 88 in FR3 might play a key role in maintaining the stability of the CDR3 antibody. The small-sized CDR3 domain antibody might act as a new scaffold for affinity transfer, hence making a useful contribution to the understanding of antigen–antibody interactions.